Behavior-Driven Development: An Expert Panel to Evaluate Benefits and Challenges - Nascimento, Nicolas; Santos, Alan R.; Sales, Afonso; Chanin, Rafael (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Teaching modern software techniques is a challenging task as these practices tend to be collaborative and require a lot of preparation and environment setup. Among these techniques is Behavior-Driven Development (BDD), a development method which proposes software to be develop focusing primarily on its expected behavior. In this context, this paper investigates the perception of active-learning experts regarding the potential benefits and challenges of teaching BDD in active learning environments to software engineering students. To achieve this goal, we have conducted an expert panel with 28 active-learning experts from four countries. Our preliminary results indicate that experts perceive both benefits, like improvement in specification, and challenges to embrace the BDD "culture" when teaching BDD to software engineering students. Based in these findings, we found indicatives that BDD should benefit software engineering students in active learning environments, however it may require more setup, teacher preparation and engagement during the learning process.